Biomass‐derived ant colony‐like ion diffused redox porous carbon toward economical and high‐performance quasi‐solid‐state supercapacitor. (15th September 2021) - Shankar, Edugulla Girija; Das, Amit Kumar; Yu, Jae Su
Summary: Present work successfully demonstrates the synthesis of ion diffused ant colony‐like porous carbon structure (PSWC) with high surface roughness from seaweed using a facile pre‐carbonization NaCl treatment, followed by carbonization at 800°C. X‐ray photoelectron spectroscopy and energy‐dispersive X‐ray spectroscopy studies confirm the retention of natural redox groups such as pyrrolic N, pyridinic N, oxidized sulfur, carboxyl, Fe 3+, and Zn 2+ and the diffusion of Na + and Cl − ions in the PSWC. The electrochemical analysis of PSWC reveals that NaCl treatment further enhances the performance, and the redox groups and transition metal ions facilitate the faradic battery‐type energy storage with an excellent specific capacitance of 904.44 F g −1 at 1 A g −1 of current density in a classic three‐electrode system. The fabricated polyvinyl alcohol‐potassium hydroxide gel electrolyte‐based quasi‐solid‐state asymmetric supercapacitor device exhibits good energy density and power density of 52.15 Wh kg −1 and 362.14 W Kg −1, respectively with a superior cyclic life (98.94% capacitance retention after 10 000 cycles). The overall eco‐friendliness, low cost, availability, facile synthesis process, sustainability, facile upscale synthesis, and excellent electrochemical properties provide a potential application of PSWC in advanced energy storage systems. Abstract : Seaweed‐derived ant colony‐like porous carbon‐based eco‐friendly quasi‐solid‐state asymmetric supercapacitor, exhibiting excellent electrochemical performance, is explored for potential application in a practical energy storage system.